Movement Analysis of Fundamental Forehand and Backhand Tennis Techniques for Athletes at the Sekadau Regency PELTI Introductory Tennis Club - Ilham Perani; Ade Rahmat; Suriani Sari (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. The objective of this study is to assess the fundamental forehand and backhand tennis movement competencies for beginner PLTI tennis players in the Sekadau district. Materials and methods. The study utilized observation, interviews, and questionnaires as primary data sources. Secondary data included documentation and training session attendance records. Triangulation was employed in data collection through observation, interviews, and questionnaires. Data analysis adhered to Miles and Huberman's interactive model, involving data collection, reduction, presentation, and conclusion drawing. Observational data revealed athletes' deficiencies in foot and hand positioning during racket swings. Interviews indicated that training processes were hindered by issues such as non-standard balls, management difficulties, and athlete distractibility. Results. The questionnaire results revealed insufficient performance by athletes, especially in question 7 about foot positioning in forehand and backhand techniques. Thus, the data imply a lack of fundamental proficiency in forehand and backhand technical movements among PELTI tennis court athletes at Sekadau Regency Beginners. Conclusions. The examination of Forehand and Backhand competencies in Field Tennis for PELTI novice athletes in Sekadau district is inadequate. Observational and interview findings reveal subpar performance metrics. Numerous athletes attain scores that are deemed insufficient and unsatisfactory.